The lie you don't know you believe : how to find it, fight it, & live free - Allen, Jennie (Nelson Books, 2026)
"If there was a core lie sabotaging your life, wouldn't you want to know what it is? And wouldn't you want to find the way to be free?"-- Provided by publisher.